ChemInform Abstract: Convenient One‐Pot Synthesis of α‐Amino Phosphonates in Water Using p‐Toluenesulfonic Acid as Catalyst for the Kabachnik—Fields Reaction. Issue 29 (1st July 2013) - Wu, Mingshu; Liu, Rendie; Wan, Dehui
Abstract: The title compounds (IV) are obtained in a three‐component reaction of substituted salicylaldehydes, aromatic amines, and triphenyl phosphite under mild and green reaction conditions.